2020
DOI: 10.21873/invivo.11805
|View full text |Cite
|
Sign up to set email alerts
|

Is Ovarian Tissue Transport at Supra-zero Temperatures Compared to Body Temperature Optimal for Follicle Survival?

Abstract: Background/Aim: Transportation of ovarian cortex prior to freezing is used clinically; however, basic investigations of ovarian storage are limited and the question remains what temperature is optimal for transport over long distances and time periods. The aim of this study was to evaluate the rate of follicular loss over various time periods under two different temperatures and assess whether ovarian follicle viability is affected following cryopreservation and thawing subsequent to the transportation of ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Media used in the present study were chosen based on ovarian tissue transportation reports. IVF medium [15] and L-15 [16] are used in clinical practice in humans, while NaCl and PBS act as controls and have been used in ovarian transportation studies in different animal species [25,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Media used in the present study were chosen based on ovarian tissue transportation reports. IVF medium [15] and L-15 [16] are used in clinical practice in humans, while NaCl and PBS act as controls and have been used in ovarian transportation studies in different animal species [25,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation (using TUNEL, ISEL or other techniques) was performed in ten studies (Jewgenow et al 1997, Wongsrikeao et al 2005, Goncalves et al 2015, Kamoshita et al 2016, Cavalcante et al 2017, Gastal et al 2017, Barberino et al 2018, Piras et al 2018, Vilela et al 2020. Four studies used embryo analyses (Wongsrikeao et al 2005, Naoi et al 2007, Ribeiro et al 2008, Wang et al 2011 and five assessed isolated follicles (Lucci et al 2007, Lopes et al 2009, Lima et al 2014, Correia et al 2017, Raffel et al 2020. One study considered offspring after IVF (Kamoshita et al 2016).…”
Section: Analyses Performedmentioning
confidence: 99%
“…In pigs, studies reported reduced oocyte viability and maturation rates at low temperatures in saline solution, suggesting that porcine ovaries should be stored for a short time (<6 hours) at 25-35°C (Wongsrikeao et al 2005, Tellado et al 2014. In PBS, follicle viability declined over time, even at 4°C, but follicle morphology remained similar to fresh controls for up to 12 hours (Raffel et al 2020).…”
Section: Effects On Oocyte Maturation and Fertilization And Embryo Pmentioning
confidence: 99%
“…In 1998, it was also the earliest basis of current slow freezing technology. Raffel, N., et al [7]. used the slow freezing method to freeze the ovarian tissue of sheep, and got successfully pregnant after auto transplantation, which provided a good model for human ovarian tissue freezing and transplantation.…”
Section: Freezing and Resuscitation Of Ovarian Tissuementioning
confidence: 99%